Modelling of interfacial friction damping of carbon nanotube-based nanocomposites - Lin, R.; Lu, Chungsheng (Academic Press, 2010)
Carbon nanotube-based composite is becoming increasingly popular and offers great potential for highly demanding practical high strength and high damping applications. The excellent damping capacity of CNTs is primarily due to the interfacial friction between carbon nanotubes and polymer resins and the extremely large interfacial surface area over a given specific mass (specific area). In this paper, damping characteristics of carbon nanotube-based composites have been investigated, with an objective of developing an effective and accurate analytical model, which can be used as a design tool for the damping design of such materials. Based on the interfacial slips between the resin and nanotubes and between the nanotubes themselves, a micro stick-slip damping model has been developed. Such a physically derived model is believed to be appropriate and representative of the actual complex damping mechanism of the material system. The model, developed for the first time, is analytical and relates explicitly the material properties of the resin and nanotubes and the processing parameters to the overall material damping loss factor and hence it offers the possibility for material engineers to possibly optimize the damping for required applications.Due to the nonlinear force–displacement relationship derived under the micro stick-slip, a harmonic linearization method, the Describing Function method, has been employed to analyse its vibration characteristics and to derive the required damping loss factors. From the analytical formula, it can be seen that the damping loss factor of the material system depends on the individual material properties of the resin and the nanotubes, structural deformation, nanotube volume fraction and the critical shear stresses at which interfacial slips take place. By taking careful considerations of these design parameters, optimized carbon nanotube-based composites for advanced damping applications can be developed. Extensive numerical simulations have been carried out to establish the practical applicability of the proposed analytical model. Based on realistic material properties of carbon nanotubes and polymer resins, damping characteristics have been predicted which compare well with existing results from open literature. The results have shown that for a volume fraction as small as 1%, a damping loss factor as high as 20% can be achieved which is adequate for most practical applications. The model has been further developed to deal with bending vibrations where different parts of the material are subject to different vibration strain levels. A practical case of cantilevered beam vibration has been employed to demonstrate the practical application of the proposed model.